Analysis of Teacher Perceptions of the Implementation of the Merdeka Curriculum in Hindu Religious Education Subjects at Karangasem Regency High School - Sudiarta, I Wayan (Jurnal Penelitian Agama Hindu, 2024)
Implementing the Merdeka curriculum is an essential factor in learning, and collaboration between teachers, schools, and related parties is needed to implement the Merdeka curriculum, especially in Hindu Religious Education subjects. Hindu religious education is the content of the school curriculum, which plays a role in building student character. However, there are still obstacles to implementing the Merdeka curriculum. Namely, students still need to be more active and listen to what the teacher says. There are limited learning resources, so learning is still teacher-centered. This research aims to describe teachers' perceptions of implementing the Merdeka curriculum in Hindu Religious Education subjects. This type of research is quantitative with a descriptive approach. This research method is a survey. The data collection technique uses a questionnaire via Google Forms. The population in this study were 10 Hindu Religious Education teachers at SMA Karangasem Regency. The data analysis technique uses quantitative descriptive analysis presented in percentage form. The research results show that teachers' perceptions of implementing the Merdeka curriculum in Hindu Religious Education subjects are perfect. The data obtained is based on an analysis of the percentage of teachers' perceptions who agree and strongly agree, are very precise and appropriate, and are very relevant and relevant to the implementation of the Merdeka curriculum, so this research will have an impact on improving teaching and understanding of Hindu Religious Education in a more contextual and relevant way for students.